The Effect of Adding Gotu Kola Leaves (Centella asiatica L.) on the Nutrient Content of Tilapia Fish Meatballs (Oreochromis niloticus) as a Healthy Snack for Teenagers - Selinda Mahdalia; Rieska Indah Mulyani; Astri Ayu Novaria; Yulian Andriyani (PT FORMOSA CENDEKIA GLOBAL, 2023)
One of the eating behaviors in teenagers is the habit of snacking in the form of snacks. Snacks have a negative impact if consumed excessively, namely they can cause excess energy intake. The aim of this research was to determine the sensory evaluation and nutritional content of tilapia fish meatballs with the addition of gotu kola leaf flour. This research used a Completely Randomized Design (CRD) with four treatments and three repetitions. Four treatments were used in making fish meatballs with the addition of gotu kola leaf flour, namely 10 gr; 15 gr; 20 gr; 25 gr. The results of the research showed that the best fish meatballs were the treatment concentration of 5% gotu kola leaf flour which had an energy content of 223.37 kcal, protein 45.2 grams, fat 0.29 grams, carbohydrates 10.08 grams, water content 62.8%, ash content 1.33% and fiber 2.36%.